2011
DOI: 10.1021/jo2018735
|View full text |Cite
|
Sign up to set email alerts
|

Electroreductive Intramolecular Coupling of Phthalimides with Aromatic Aldehydes: Application to the Synthesis of Lennoxamine

Abstract: The electroreductive intramolecular coupling of phthalimides with aromatic aldehydes in the presence of chlorotrimethylsilane and triethylamine led to five-, six-, and seven-membered cyclized products (58-84%). The electroreductive cyclization was applied to the total synthesis of lennoxamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…599602 As an application of the TMSCl promoted electroreductive coupling, Kise and co-workers utilized an intramolecular coupling between an aldehyde and a phthalimide to synthesize lennoxamine in a concise fashion (Figure 38B, bottom). 603 …”
Section: Cathodic Reductionmentioning
confidence: 99%
“…599602 As an application of the TMSCl promoted electroreductive coupling, Kise and co-workers utilized an intramolecular coupling between an aldehyde and a phthalimide to synthesize lennoxamine in a concise fashion (Figure 38B, bottom). 603 …”
Section: Cathodic Reductionmentioning
confidence: 99%
“…DFT calculations suggested that the C­(sp 3 )–H bond was cleaved prior to the C­(sp 2 )–H bond of the ketimine, which was different from many other Rh-catalyzed C–H cyclization reactions . Notably, this protocol provides an efficient and reliable approach to 3-methyleneisoindolin-1-ones, which not only are key structure motifs in a myriad of nature products but also serve as important building blocks for the synthesis of important pharmaceuticals …”
Section: Introductionmentioning
confidence: 93%
“…Imides can react intermolecularly with α,β‐unsaturated esters, oximes and carbonyls to afford polycyclic lactams . The latter strategy was used by the Kise laboratory in a key step in the total synthesis of lennoxamine (Scheme ) . Here, cathodic reduction of aldehyde 184 in the presence of chlorotrimethylsilane and triethylamine afforded the pentacyclic lactam 185 , which was converted into lennoxamine in five steps.…”
Section: Cathodic Reductionmentioning
confidence: 99%